Epigenetic information in gene expression and cancer - Kurdistani, Siavash (Henry Stewart Talks, 2007)
Types and functions of histone modifications, Histone code hypothesis, Epigenetics and transcription regulation, Relevance for human disease
Archived at 2021/02/25